Feasibility and effectiveness of tools that support communication and decision making in life-prolonging treatments for patients in hospital: a systematic review. Issue 3 (5th October 2020) - Thodé, Maureen; Pasman, H Roeline W; van Vliet, Liesbeth M; Damman, Olga C; Ket, Johannes C F; Francke, Anneke L; Jongerden, Irene P
Abstract : Objective: Patients with advanced diseases and frail older adults often face decisions regarding life-prolonging treatment. Our aim was to provide an overview of the feasibility and effectiveness of tools that support communication between healthcare professionals and patients regarding decisions on life-prolonging treatments in hospital settings. Design: Systematic review: We searched PubMed, CINAHL, PsycINFO, Embase, Cochrane Library and Google Scholar (2009–2019) to identify studies that reported feasibility or effectiveness of tools that support communication about life-prolonging treatments in adult patients with advanced diseases or frail older adults in hospital settings. The Mixed Methods Appraisal Tool was used for quality appraisal of the included studies. Results: Seven studies were included, all involving patients with advanced cancer. The overall methodological quality of the included studies was moderate to high. Five studies described question prompt lists (QPLs), either as a stand-alone tool or as part of a multifaceted programme; two studies described decision aids (DAs). All QPLs and one DA were considered feasible by both patients with advanced cancer and healthcare professionals. Two studies reported on the effectiveness of QPL use, revealing a decrease in patient anxiety and an increase in cues for discussing end-of-life care with physicians. The effectiveness of one DA was reported; it led to more understanding of the treatment in patients. Conclusions: Use of QPLs or DAs, as a single intervention or part of a programme, may help in communicating about treatment options with patients, which is an important precondition for making informed decisions.